ANALYSIS OF NAME LOAN AGREEMENT IN THE PERSPECTIVE OF FREEDOM OF CONTRACT - Bastian, Benny (ANAYASA : Journal of Legal Studies, 2025)
Nominee agreements are one of the interesting legal issues in the Indonesian legal system, especially in the context of acquiring land ownership rights. This practice is often used to avoid various applicable legal restrictions, both related to the legal subject and the land use itself. In agrarian law, land ownership rights can only be owned by Indonesian citizens (WNI), as regulated in Law Number 5 of 1960 concerning Basic Agrarian Principles (UUPA). However, nominee agreements are often used to get around mandatory legal provisions, thus raising questions about their validity from the perspective of freedom of contract. This study aims to analyze the legality of nominee agreements between Indonesian citizens concerning acquiring land ownership rights, using a descriptive qualitative approach. The data were analyzed based on the provisions of the Civil Code (KUHPerdata), especially Articles 1320 and 1338 which regulate the requirements for the validity of agreements and the principle of freedom of contract. The results of the analysis show that although a name-borrowing agreement can be made based on an agreement between the parties, objectives that are contrary to the law make this agreement legally invalid. This practice also violates the principle of freedom of contract because it is used to smuggle coercive legal provisions. The legal consequences of a name-borrowing agreement are null and void so the rights and obligations arising from the agreement are not recognized. In conclusion, the title loan agreement cannot be legally protected and has the potential to pose legal risks to the land objects involved. Therefore, legal protection can only be given to agreements made per applicable legal provisions.